The relationship between occupational participation, meaningful activity and quality of life of colorectal cancer survivors / Musaropah Sapihis - Musaropah, Sapihis (2018)
BACKGROUND: Globally, colorectal cancer is the third most common type of cancer, constituting about ten percent of all cases and affecting mostly older adults. Previous studies on the Quality of life (QoL) of colorectal cancer survivors have not focused on the area of participation in daily living activities. Occupational participation is an essential concept and a key significant outcome in the field of occupational therapy. This study aim is to explore the relationships between colorectal cancer (CRC) survivors’ occupational participation, meaningful activity and their QoL. METHOD: This is 2-phase study using structural equation modelling, and a theoretical model based on an occupational perspective to examine potential mechanisms of the mediation effect of meaningful activity on QoL. Upon ethical approval from University Malaya Medical Centre Ethic Committee, data were collected from two public hospitals. Face to face interview were conducted using the Malay version of Occupational Participation Questionnaire (OPQ-M), Engagement in Meaningful Activities Survey (EMAS-M) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire version 3.0 (EORTC QLQ-C30). Data analyses for testing the proposed research hypotheses were done using Partial least square structural equation modelling (PLS-SEM) techniques. RESULTS: 113 participants were completed the questionnaires from a total of 152 consented participants. The mean age of the survivors was 64.7 (SD=10.4) years and range from 18 to 75 years. A significant weak positive association was found between overall score of occupational participation and QoL (r=0.35; p<0.05). Significant positive association were found between i) total score of iv meaningful activity and QoL (r=0.62; p<0.0 5) and ii) total score of meaningful activity and occupational participation (r=0.45; p<0.05).The five most significant restrictions to occupational participation were in activities of working full or part time (70%), performing voluntary work (51.3%), participating in sport activities (40.7%), travelling for pleasure (34.5%) and activities helping and support others (22.1%).The predictors of QoL for CRC survivors were occupational participation and meaningful activity, which comprises a variance of 43.7 percent. The model of occupational participation, meaningful activity and QoL (OP-MA-QoL) has sufficient predictive relevance (Q2 ) with values between, 0.471 to 0.612 (Q2>0). Mediation analyses confirmed that meaningful activity served as a significant mediator between occupational participation and QoL (β=0.284(a*b), ρ<0.01, SE=0.05, z=5.040, ρ<0.01). CONCLUSION: This study found a positive, preliminary hypothesised OP-MA-QoL model, where meaningful activity mediates the fulfilment of occupational participation, which in turn positively influence QoL of the CRC survivors. Findings can inform the planning of occupational therapists in their Occupational-based intervention. Further research using longitudinal data and all stakeholders such as caregivers report are needed to re-examine this preliminary model